Enhanced polyethylene terephthalate (PET) glycolysis with biochar-supported organic ionic liquid-based catalysts - Stuart Conroy; Fraser Norris; Elliot Ross; Stuart D. Robertson; Yong Xu; Ashleigh J. Fletcher; Xiaolei Zhang (Journal of Environmental Chemical Engineering, 2026)

Transgenerational plasticity responses differ across genetically distinct families in the Sydney rock oyster, Saccostrea glomerata - Laura M. Parker; Elliot Scanes; Wayne A. O'Connor; Michael Dove; Thiyagarajan Vengatesen; Steven Roberts; Pauline M. Ross (Marine Environmental Research, 2025)

The long-lived deep-sea bivalve Acesta excavata is sensitive to the dual stressors of sediment and warming - Elliot Scanes; Tina Kutti; James K.H. Fang; Emma L. Johnston; Pauline M. Ross; Raymond J. Bannister (Marine Pollution Bulletin, 2024)

Resilience against the impacts of climate change in an ecologically and economically significant native oyster - Laura M. Parker; Elliot Scanes; Wayne A. O'Connor; Michael Dove; Abigail Elizur; Hans-Otto Pörtner; Pauline M. Ross (Marine Pollution Bulletin, 2024)

Extending conservation of coastal and oyster reef restoration for First Nations cultural revitalization - Mitchell Gibbs; Pauline Ross; Elliot Scanes; James Gibbs; Raphaela Rotolo‐Ross; Laura Parker (Conservation Biology, 2023)

Transgenerational transfer of the microbiome is altered by ocean acidification in oyster larvae - Elliot Scanes; Pauline M. Ross; Justin R. Seymour; Nachshon Siboni; Michael C. Dove; Wayne A. O'Connor; Callum Dittes; Laura M. Parker (Aquaculture, 2023)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Cover Image: Volume 25 Number 3, March 2022 - Joseph A. Tobias; Catherine Sheard; Alex L. Pigot; Adam J. M. Devenish; Jingyi Yang; Ferran Sayol; Montague H. C. Neate‐Clegg; Nico Alioravainen; Thomas L. Weeks; Robert A. Barber; Patrick A. Walkden; Hannah E. A. MacGregor; et al. (Ecology Letters, 2022)

AVONET: morphological, ecological and geographical data for all birds - Joseph A. Tobias; Catherine Sheard; Alex L. Pigot; Adam J. M. Devenish; Jingyi Yang; Ferran Sayol; Montague H. C. Neate‐Clegg; Nico Alioravainen; Thomas L. Weeks; Robert A. Barber; Patrick A. Walkden; Hannah E. A. MacGregor; et al. (Ecology Letters, 2022)
Functional traits offer a rich quantitative framework for developing and testing theories in evolutionary biology, ecology and ecosystem science. However, the potential of functional traits to drive theoretical advances and refine models of global change can only be fully realised when species‐level information is complete. Here we present the AVONET dataset containing comprehensive functional trait data for all birds, including six ecological variables, 11 continuous morphological traits, and information on range size and location. Raw morphological measurements are presented from 90,020 individuals of 11,009 extant bird species sampled from 181 countries. These data are also summarised as species averages in three taxonomic formats, allowing integration with a global phylogeny, geographical range maps, IUCN Red List data and the eBird citizen science database. The AVONET dataset provides the most detailed picture of continuous trait variation for any major radiation of organisms, offering a global template for testing hypotheses and exploring the evolutionary origins, structure and functioning of biodiversity.

Nicotinic receptor modulation of the default mode network - Britta Hahn; Alexander N. Harvey; Marta Concheiro-Guisan; Marilyn A. Huestis; Thomas J. Ross; Elliot A. Stein (Psychopharmacology, 2021)

Mine Waste and Acute Warming Induce Energetic Stress in the Deep-Sea Sponge Geodia atlantica and Coral Primnoa resedeaformis; Results From a Mesocosm Study - Elliot Scanes; Tina Kutti; James K. H. Fang; Emma L. Johnston; Pauline M. Ross; Raymond J. Bannister (Frontiers in Marine Science, 2018)

Ocean acidification affects both the predator and prey to alter interactions between the oyster Crassostrea gigas (Thunberg, 1793) and the whelk Tenguella marginalba (Blainville, 1832) - John M. Wright; Laura M. Parker; Wayne A. O’Connor; Elliot Scanes; Pauline M. Ross (Marine Biology, 2018)

Effects of multiple climate change stressors: ocean acidification interacts with warming, hyposalinity, and low food supply on the larvae of the brooding flat oyster Ostrea angasi - Victoria J. Cole; Laura M. Parker; Stephen J. O’Connor; Wayne A. O’Connor; Elliot Scanes; Maria Byrne; Pauline M. Ross (Marine Biology, 2016)

Insula’s functional connectivity with ventromedial prefrontal cortex mediates the impact of trait alexithymia on state tobacco craving - Matthew T. Sutherland; Allison J. Carroll; Betty Jo Salmeron; Thomas J. Ross; Elliot A. Stein (Psychopharmacology, 2013)

Chronic smoking, but not acute nicotine administration, modulates neural correlates of working memory - Matthew T. Sutherland; Thomas J. Ross; Diaá M. Shakleya; Marilyn A. Huestis; Elliot A. Stein (Psychopharmacology, 2011)

Nicotine modulation of information processing is not limited to input (attention) but extends to output (intention) - Emma J. Rose; Thomas J. Ross; Pradeep K. Kurup; Elliot A. Stein (Psychopharmacology, 2010)